(untitled) (Medical Forum Monthly, 2022)
Objective: To assess the perception of women regarding breast feeding and lactation during Covid 19 pandemic. Study Design: Cross-sectional descriptive study. Place and Duration of Study: This study was conducted at the obstetrics and gynecology Department, neonatal follow-up clinics and vaccination center at Darul Sehat Hospital Karachi from September 2021 to November 2021. Materials and Methods: A questionnaire was introduced to women after taking informed consent. Included females were either lactating currently or practicing since last six month and those with breast feeding problems were excluded from study. Questionnaire contain three portions of which first part inquired about demographic features, second part contained questions about perception and third part is about practices of breast feeding during Covid -19 pandemic. Data was analyzed using IBM-SPSS version 23.0. Means with standard deviation were given for quantitative variables and chi square test is used to assess association between perception of breast feeding and different study variables. Results: The study included 206 participants. Mean age was 28.8 years (SD ±5.0). 66.2% suggested breastfeeding should continue even in covid prevalent communities, 33.8% claimed that covid virus can be transmitted via breastfeeding, 57.6% said wearing a mask should be mandatory while breastfeeding and 84.3% suggested washing hands prior to breastfeeding helps prevent transmission of virus from mother to baby. 66.2% thought breastfeeding protects the child against covid disease. Conclusion: Covid 19 pandemic has affected breastfeeding practices. Majority women suggested breastfeeding should continue even in communities where covid is pandemic, and that breastfeeding protects the child against covid disease.